Trans-Pacific partnership rules for digital trade in Asia - Deborah Elms; Minh Hue Nguyen (Asian Development Bank Institute (ADBI), 2017)
Digital trade is upending the way consumers and companies do business. Digital trade and e-commerce have become major drivers of economic development by enhancing productivity and lowering costs of trade in goods. But government policies have been slow to catch up with the increasing importance of cross-border data flows and the way that domestic regulations can help or hinder trade internationally. The first trade agreement to consider the importance of digital trade, the Trans-Pacific Partnership (TPP), introduced several new rules that deal with these critical issues. Why did seven Asian countries (Australia, Brunei, Japan, Malaysia, New Zealand, Singapore and Viet Nam) in the TPP with very different domestic policies in place to address digital trade and e-commerce agree to follow a similar set of policies for the sector?
Keywords: F13; 330; digital trade; TPP; Asia; free trade agreement